2017
DOI: 10.1071/rdv29n1ab19
|View full text |Cite
|
Sign up to set email alerts
|

19 a Novel Approach to Comparing Reproductive Stage Serum Profiles in Mares Using Near-Infrared Spectroscopy and Aquaphotomics

Abstract: The capability of near-infrared spectroscopy (NIR) to detect biomolecules in aqueous solutions, a sub-field of NIR called aquaphotomics, has yet to be fully explored. Aquaphotomics references water absorbance patterns and wavelength shifts in the 1st overtone of the water spectrum as they change patterns with solute composition and concentrations. Recently, NIR was used as a rapid method for detecting oestrus in Holstein raw milk and for monitoring reproductive stages in urine of the Bornean Orangutan (Pongo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The water spectral patterns of blood, milk, and urine of mastitic cows, revealed that the same water absorbance bands are activated in different body fluids in response to the presence of disease [81]. Similarly, physiological changes such as ovulation can be detected in various body fluids using the same principles such as in the Giant panda [68,83], in the Bornean orangutan [84], in dairy cows [85] and in mares [86].…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…The water spectral patterns of blood, milk, and urine of mastitic cows, revealed that the same water absorbance bands are activated in different body fluids in response to the presence of disease [81]. Similarly, physiological changes such as ovulation can be detected in various body fluids using the same principles such as in the Giant panda [68,83], in the Bornean orangutan [84], in dairy cows [85] and in mares [86].…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…Based on the PLS-PCA method, this study showed that the female panda’s small estrous hormone concentration was measured and detected using water absorbance bands in the range of 1,300 nm to 1,600 nm, and the aquagram showed these changes ( Kinoshita et al., 2012b , 2015 ). Using first derivative pretreatment and PLS-PCA method with cross-validation models, another study has managed to detect estrous cycle stages by horse blood serum through NIRS and aquaphotomics ( Agcanas et al., 2017 ; Vance et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%